Achieving cloud computing efficiency using VM Migration - Jagga, Ankit (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Cloud computing is a paradigm now days frequently used to access resources from shared pool. Resources are being accessed concurrently and hence waiting time is significantly reduced due to presence of simultaneous access. Malicious entry within cloud will be a threat required to be blocked and for this purpose cloud security consideration as a service is critical. Although cloud is supposed to possess infinite resources but still load or any of the malicious activity can cause virtual machine within cloud to fail. Virtual machine migration is initiated as the failure takes place within current virtual machine. This paper purposes a mechanism for enhancing security during migration of job to the targeted virtual machine. Redundancy tackling mechanism is present to tackle the similar content migration to targeted machine resulting in decrease in downtime and migration time. The result in terms of key size also show improvement than existing migration strategies.